A Study of Near Field Communication (NFC) Technology: A Case Study of Youth Awareness in U.P. (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The use of NFC is presently nascent in India, and not much known about its advantages. On the other hand, smart service applications and the general usage of digital technology are the main causes of the rise in electronic payments. Reliance on cash and credit cards is decreased by the availability of popular NFC payment applications like Google Pay, Paytm, Phone Pe, and Amazon Pay, which enable safely and conveniently digital transactions. The purpose of this paper is to study the influence of NFC on sociodemographic characteristics and the degree of awareness among young consumers in Sultanpur and Lucknow, Uttar Pradesh. Techniques for convenience sampling were applied. A questionnaire made with Google Forms was used to collect study data and the sample size was 222. Findings indicate that respondents in Sultanpur and Lucknow expressed an intense preference for and awareness of NFC mobile payments, which they utilize for a variety of transactions like clothing, groceries, and airline tickets. The vast majority of respondents (18–24 years old) attend KNIPSS and live mostly in Sultanpur; their educational backgrounds have not much impact on the payments they make. Thus, the results of this study may be utilized by policymakers to better formulate NFC policies in the future. This study is unique as no researcher has examined the degree of NFC mobile payment awareness in Uttar Pradesh, where the nation is still developing its NFC technological capabilities.